2011
DOI: 10.3354/meps09045
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the parasitic copepod Lepeophtheirus salmonis throughout the Atlantic

Abstract: The parasitic copepod Lepeophtheirus salmonis is responsible for huge economic losses in the salmonid aquaculture industry, and has been linked with declines of wild salmonid populations. In order to elucidate population genetic structure throughout the Atlantic Ocean, 2495 lice representing 27 samples collected from 22 locations were analysed for 14 microsatellite loci. Significant overall genetic variation was observed (14 loci: global F ST = 0.0057, p < 0.0001), although this decreased slightly when an outl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 51 publications
9
46
0
Order By: Relevance
“…However, the increase in variability from the wild 24 × data set to the wild 36 × data set was surprisingly low considering that the wild 24 × data sets were generated from single localities whereas the wild 36 × data sets contained reads from all localities. This suggests that most of the variable sites are found throughout the North Atlantic, supporting earlier studies indicating that L. salmonis displays a high degree of gene-flow, consistent with a species that can disperse at both planktonic and adult stages (Glover et al 2011). The homogeneous level of sequence variability in the 36 × data sets compared with the smaller data sets, that all stem from single sequencing runs, is probably the result of the bootstrapping procedure averaging variability among sequencing runs, which in turn indicates that the error rate variation between sequencing runs is noticeable.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the increase in variability from the wild 24 × data set to the wild 36 × data set was surprisingly low considering that the wild 24 × data sets were generated from single localities whereas the wild 36 × data sets contained reads from all localities. This suggests that most of the variable sites are found throughout the North Atlantic, supporting earlier studies indicating that L. salmonis displays a high degree of gene-flow, consistent with a species that can disperse at both planktonic and adult stages (Glover et al 2011). The homogeneous level of sequence variability in the 36 × data sets compared with the smaller data sets, that all stem from single sequencing runs, is probably the result of the bootstrapping procedure averaging variability among sequencing runs, which in turn indicates that the error rate variation between sequencing runs is noticeable.…”
Section: Discussionsupporting
confidence: 86%
“…This appears to confirm the reduced sequence variation in the inbred strain reported earlier (Hamre et al 2009) and later supported by analyses using an expanded set of microsatellites (12 out of 13 microsatellites were fixed, the last had two alleles, data not shown) following methods previously reported (Glover et al 2011). The apparent large remaining sequence variability in the inbred strain seems surprising if microsatellite variability is a reliable proxy of genetic variation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, the fit of our data to universal models of temperature dependence suggests that faster than expected development times to the infective stage may not have occurred yet, or the genetic change has not spread to all lice populations yet. However, the salmon louse has a huge spread potential, and evidence suggests a panmictic population (Glover et al 2011). Therefore, any genetic changes would spread within a few years (Besnier et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To gain insights into adaptive coevolutionary processes at ecological timescales and moreover to gain direct information on selective processes involving the interactions of individuals with their environment, higher resolution can often be achieved with functional markers that are under selection. Several studies have shown that the proportion of quantitative trait variation at the population level is much higher than it is for neutral markers (Conover et al, 2006;Glover et al, 2011;Hemmer-Hansen et al, 2007;Nielsen et al, 2009;Westgaard and Fevolden, 2007). Thus far, nonneutral markers have only been applied in potential fish host species; there are no data available on parasites.…”
Section: What Can Functional Markers Tell Us About Local Adaptations mentioning
confidence: 95%